Ultrabright and narrowband intra-fiber biphoton source at ultralow pump power. (1st January 2023) - Bruns, Alexander; Hsu, Chia-Yu; Stryzhenko, Sergiy; Giese, Enno; Yatsenko, Leonid P; Yu, Ite A; Halfmann, Thomas; Peters, Thorsten
Abstract: Nonclassical photon sources of high brightness are key components of quantum communication technologies. We here demonstrate the generation of narrowband, nonclassical photon pairs by employing spontaneous four-wave mixing in an optically-dense ensemble of cold atoms within a hollow-core fiber. The brightness of our source approaches the limit of achievable generated spectral brightness at which successive photon pairs start to overlap in time. For a generated spectral brightness per pump power of up to 2 × 10 9 pairs/(s MHz mW) we observe nonclassical correlations at pump powers below 100 nW and a narrow bandwidth of 2 π × 6.5 MHz. In this regime we demonstrate that our source can be used as a heralded single-photon source. By further increasing the brightness we enter the regime where successive photon pairs start to overlap in time and the cross-correlation approaches a limit corresponding to thermal statistics. Our approach of combining the advantages of atomic ensembles and waveguide environments is an important step toward photonic quantum networks of ensemble-based elements.